Identification Of Brain-derived Neurotrophic Factor (Bdnf) Val66met Gene Polymorphism As A Biomarker On Cognitive Performance Of Aging Brain In Response To An 8-week Of Exergames Training - Ismail, Noor Azila (2023)
The BDNF Val66Met gene polymorphism is a plausible factor for the changes in cognitive performance of the aging brain with Met carriers showed a greater impairment in cognitive ability. Therefore, study 1 examined the distribution of BDNF Val66Met gene polymorphism in the aging population and its association with cognitive performance. 206 older adults aged 55 – 80 years were enrolled in the study and divided based on their Mini Mental State Examination (MMSE) score: control group (MMSE > 26; n = 103) and case group (MMSE £ 26; n = 103). The results showed that the distribution of BDNF Val66Met gene polymorphism was significantly different between the studied groups. Conversely, the BDNF genotype was associated with a twofold risk of cognitive impairment. Therefore, Study 2 was conducted to examine the effect of the BDNF Val66Met gene polymorphism on cognitive performance in the aging brain in response to 8 weeks of exergames training. 42 participants from the case group in study 1 were subjected to 3 groups with different training methods for 30 minutes, 3 days per week for 8 weeks: exergames (training with Ring Fit Adventure for Nintendo Switch; n = 14), conventional training (similar training without exergames; n = 14), and control group (no training; n = 14). The results showed that neuropsychological test scores had significant differences between the studied groups. fMRI analysis showed that more brain areas with greater activation were detected in the exergames group as compared to the conventional group. With respect to BDNF genotype, a repeated measure of ANOVA revealed that cognitive performance was better in the ValVal genotypes on MoCA scores, and hippocampal volume tended to improve after the exergames intervention. In addition, the Met allele was associated with an improvement in neuropsychological test scores in response to both types of exercise training. Although the intervention did not produce overall improvements, there were interesting trends in the data for the ValVal genotype after exergames training. This demonstrates that exergames training appears to be an appealing and promising means of concurrent physical-cognitive training in the aging population.